The effect of "Live high, train low" on the hypoxic ventilatory response in well-trained cyclists - Townsend, N. E. (International Altitude Training Symposium 2001 - Proceedings summary, 2001)
Unkommentierte Folien der Powerpoint-Präsentation des Verf., gehalten auf dem Höhentrainingssysmposium des HASTC in Flagstaff im Frühjahr 2001.